The Deoband madrassah movement: countercultural trends and tendencies - Moj, Muhammad (Diversity and plurality in South Asia, 2015)
This innovative book analyses the growth of Deobandi Islam, a religious sect whose followers include extremist groups, through the frame of a counterculture in conflict with mainstream Muslim society. Due to its relationship with the Taliban, close links to al-Qaeda, and worldwide reach through the 'Tablighi Jamaat' (Proselytization Group), the Deoband Madrassah Movement has come to acquire global significance. In Pakistan, Deobandi schools have increasingly been associated with the rise of an intolerant and militant strain of Islam linked with terrorist activities.